Internal and external factors of mental health disorders in a healthy sustainable soul according to islamic psychotherapy in smart campus perspective - Rahman, Zaizul Ab; Abdul Kadir, Fakhrul Adabi; Mansor, Nurul Husna; Razick, Ahamed Sarjoon; Yusoff, Hanizah Mohd (IAEME Publication, 2018)
God's Word s.w.t: Then set your face straight to the religion of Allah, the nature of Allah, which He created man above that nature; there is no change for the creation of the nature of God; that's a straight religion, but most people do not know it. Every child born is in a sacred state, then both parents make it Jewish, Christian or Majusi. (HR Bukhari from Abu Hurairah r.a). Every human being who has been born to this earth has been created in the natural state; his heart always wants to face his God and wants to follow his religion; and the nature that God has created in every human being will never change, it will still voice the command to always return to the truth of God. In the growth and development of human development since birth until adulthood, nature is often lacking attention. This causes them to be unable to participate in daily activities through words, deeds, attitudes and movements. Property is the thing that is always the goal of man in the world. It sometimes causes all human life to be attracted to its enjoyment. This causes far in the corner of the natural heart to feel bound, confused, crying and disappointed because it cannot move freely to the direction of God's pleasure s.w.t. This is what causes people to become anxious, anxious and frightened.